Amino acid auxotrophies in human gut bacteria are linked to higher microbiome diversity and long-term stability - Starke, Svenja; Harris, Danielle M.M.; Zimmermann, Johannes; Schuchardt, Sven; Oumari, Mhmd; Frank, Derk; Bang, Corinna; Rosenstiel, Philip; Schreiber, Stefan; Frey, Norbert; Franke, Andre; Aden, Konrad Arnold Altfrid; et al. (The ISME journal, 2023)
Amino acid auxotrophies are prevalent among bacteria. They can govern ecological dynamics in microbial communities and indicate metabolic cross-feeding interactions among coexisting genotypes. Despite the ecological importance of auxotrophies, their distribution and impact on the diversity and function of the human gut microbiome remain poorly understood. This study performed the first systematic analysis of the distribution of amino acid auxotrophies in the human gut microbiome using a combined metabolomic, metagenomic, and metabolic modeling approach. Results showed that amino acid auxotrophies are ubiquitous in the colon microbiome, with tryptophan auxotrophy being the most common. Auxotrophy frequencies were higher for those amino acids that are also essential to the human host. Moreover, a higher overall abundance of auxotrophies was associated with greater microbiome diversity and stability, and the distribution of auxotrophs was found to be related to the human host’s metabolome, including trimethylamine oxide, small aromatic acids, and secondary bile acids. Thus, our results suggest that amino acid auxotrophies are important factors contributing to microbiome ecology and host-microbiome metabolic interactions.
Gesehen am 06.12.2023